1977
DOI: 10.1017/s000192590000809x
|View full text |Cite
|
Sign up to set email alerts
|

Some Measurements in a Turbulent Circular Jet in the Presence of a Co-flowing Free Stream

Abstract: SummaryResults obtained by hot-wire measurements in a turbulent jet are presented for the cases where the jet issues into a co-flowing free stream and, for comparison, where the jet issues into quiescent air. The results obtained in the former show some agreement with other workers, but they are more extensive, including measurements of microscales and macroscales. The results also suggest that the presence of a free stream reduces the rate of decay of the longitudinal turbulent component of velocity, which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…When the discharge is released parallel to the ambient flow, a jet in a co-flow, the flow becomes a weak-jet. Studies by Antonia and Bilger (1973), Smith and Hughes (1977), Nickels and Perry (1996), Davidson and Wang (2002) and others showed that mean cross-sectional flow profiles remain approximately Gaussian, although the entrainment rates change, requiring a modification of the spread relationship. When the discharge is released perpendicular to the ambient, a jet in a cross-flow, the flow becomes an advected line momentum puff.…”
Section: Introductionmentioning
confidence: 99%
“…When the discharge is released parallel to the ambient flow, a jet in a co-flow, the flow becomes a weak-jet. Studies by Antonia and Bilger (1973), Smith and Hughes (1977), Nickels and Perry (1996), Davidson and Wang (2002) and others showed that mean cross-sectional flow profiles remain approximately Gaussian, although the entrainment rates change, requiring a modification of the spread relationship. When the discharge is released perpendicular to the ambient, a jet in a cross-flow, the flow becomes an advected line momentum puff.…”
Section: Introductionmentioning
confidence: 99%
“…Initially he prepared for publication his earlier work on numerical solutions for high-speed laminar boundary layers over surfaces of varying temperature (184) and heat transfer measurements on surfaces exposed to high-speed turbulent boundary layers (185) . Meanwhile, he developed an interest in fluidics (186) and later became involved in the Department's programme of jet research (187,188) , of which more presently. Dogged by progressively debilitating ill health, however, his life was sadly all too short, his good judgement, fairness and dry Mancunian humour being greatly missed by all in the Department.…”
Section: The Department Of the Mechanics Of Fluids And Its Successorsmentioning
confidence: 99%
“…Schlieren images and pressure traverses from the Pannu and Johannesen notched nozzle experiments (221) indicated persistent trailing vortex pairs emanating from the notches, together with broad regions of low speed turbulent flow effectively shrouding the noise sources within the jets. Smith's involvement in this programme, initially with Hughes as mentioned above, began with experiments on sonic jets issuing into either still air or a co-flowing stream provided by the low turbulence tunnel (187) . Later experiments, in which flow from a notched nozzle issued parallel to the low-turbulence tunnel's airstream (188) , added further weight to the findings of Pannu and Johannesen (221) .…”
Section: The Department Of the Mechanics Of Fluids And Its Successorsmentioning
confidence: 99%
“…For compressible jets in a general stream, the governing equations are identical to those given in Equations (l)-(3) provided 6 is taken to be the excess temperature between the local fluid and that of the external stream, or 0 = T -T x . Equation (4) should be replaced by the perfect gas law which can be written in terms of 9 and p, under the assumption of constant pressure, as: (15) which is identical in form to Equation (4). The boundary conditions are the same as those given in Equations (5) and (6).…”
Section: Compressible Jets In a General Streammentioning
confidence: 99%